Hubungan efikasi diri dengan self-regulated learning siswa SMA dalam pembelajaran daring - Cahyaning Suryaningrum; Muhammad Firdaus Hidayatullah; Susanti Prasetyaningrum (Cognicia, 2023)
In the field of education during the pandemic, students must do online learning. The online learning process raises several problems in the form of low motivation, decreased academic achievement and grades, and less than optimal student activity during online learning to affect the less than optimal self-efficacy produced. Self-efficacy is a factor that can affect self-regulated learning in online learning. Students who have high self-efficacy, will increase student success in learning. However, if self-efficacy is low, students feel pressured in completing tasks that make it difficult to carry out learning strategies, which has an impact on self-efficacy. The purpose of this study was to determine the relationship between self-efficacy and self-regulated learning students in this online learning. The sample of this study amounted to 102 samples using accidental sampling techniques. The instruments used are the Self-Efficacy Scale and the Self-Regulated Learning Scale. The analysis technique used is the pearson product moment  correlation test. The results showed that there was a significant positive relationship between self-efficacy and self-regulated learning of r = 0.675 (p < 0.05) where the higher the self-efficacy, the higher the self-regulated learning. Keywords: High school students, online, self-efficacy, self-regulated learning